Stenting of the arterial duct combined with banding of the pulmonary arteries and atrial septectomy or septostomy: a new approach to palliation for the hypoplastic left heart syndrome. Issue 6 (June 1993) - Gibbs, J L; Wren, C; Watterson, K G; Hunter, S; Hamilton, J R
Abstract : OBJECTIVE–To assess the feasibility of pulmonary artery banding, atrial septectomy or septostomy, and percutaneous stenting of the arterial duct in babies with the hypoplastic left heart syndrome. PATIENTS–Four infants with hypoplastic left heart syndrome. SETTING–Two supraregional paediatric cardiac centres. METHODS–Ductal patency was maintained initially with prostaglandin E. Banding of the proximal branch pulmonary arteries was performed through a median sternotomy and open atrial septectomy was performed if balloon septostomy was not. Stainless steel stents (Johnson & Johnson) mounted in a balloon catheter were implanted into the arterial duct under radiographic control and expanded to a diameter of approximately 8 mm, prostaglandin treatment was then stopped. RESULTS–All the patients survived the immediate postoperative period and maintenance of wide ductal patency was achieved in three of the four patients by stent implantation. Two weeks after the procedure two babies died of right ventricular failure and respiratory infection: some distal ductal constriction had occurred in one where the stent was not quite sufficiently distally placed. One child was discharged home 15 days after treatment and was well at follow up at age 16 weeks and one was stable but required diuretic therapy five weeks after the procedure. CONCLUSIONS–This new approach is technically feasible. At least in the short term it seems to offer hope of effective palliation for the hypoplastic left heart syndrome and it warrants further study.